Combined detection of monocyte distribution width and procalcitonin for diagnosing and prognosing neonatal sepsis - Jiaping Wang; Ming Hu; Na Wang; Tingting Huang; Huiyi Wu; Hua Li (BMC Infectious Diseases)
Abstract Background To assess the value of combined Monocyte Distribution Width (MDW) and Procalcitonin (PCT) detection in diagnosing and predicting neonatal sepsis outcomes. Methods This retrospective study, conducted from January 2022 to December 2023.A retrospective analysis of 39 neonatal sepsis and 30 non-infectious systemic inflammatory response syndrome (SIRS) cases was conducted. MDW, PCT, and CRP levels were compared. Relationships between variables were analyzed with Pearson correlation and Cox regression models; diagnostic performance was assessed using ROC curves. Results MDW, PCT, and CRP were significantly elevated in sepsis cases (p < 0.001). In non-survivors, MDW was higher and correlated with CRP, PCT, and SNAP scores. MDW was identified as an independent predictor of 28-day mortality. Optimal MDW, PCT, and CRP cut-offs (21.3, 1.23 ng/ml, 32.8 mg/L) achieved AUCs of 0.80, 0.84, and 0.60, respectively. Combined MDW/PCT detection achieved an AUC of 0.90 with 88.2% sensitivity and 88.7% specificity. Conclusion MDW, especially when combined with PCT, improves diagnostic accuracy for neonatal sepsis management.